Bachelor´s dissertation at the schools of economics and business in Spain: lecturer´s perceptions - Lafuente Lechuga , Matilde; Faura Martínez, Úrsula; Puigcerver Peñalver, Mari Carmen; Bote , Marcos; Martín Castejón, Pedro Juan (Journal of Management and Business Education, 2019)
The inclusion of the Bachelor Dissertation in the curriculum of higher education leads to multiple challenges. Thus, universities adapted this course to different organizational needs. The aim of this study is to analyse the applications of the Bachelor Dissertation in the Schools of Economics and Business regarding organization, plagiarism, tutoring, evaluation and lecturer’s rewards. In order to do so a survey was passed (451 lecturers/39 schools). Results show important differences in evaluation, tutoring, and temporal involvement and the detention and penalization of plagiarism.